Framing Pesan Dakwah di Media Sosial - Primasari, Winda; Asmara Dwi Aksa, Yudha (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2017)
The development of communication and information technology is not only changing the economic, social, political, and cultural practices, but it is also changing the religious practices, including for da’wah activities called as E-da’wah (Electronic da’wah). This study attempts to investigate the construction of da’wah message used by Ustadz Felix Y. Siaw dan Ustadz Yusuf Mansur in his facebook fanpage. Using Pan and Kosicki’s framing analysis and in doing so utilizing in-depth-interview in collecting the data, this research has revealed that the most da’wah messages shared on both ustadz’s facebook fanpages are carefully constructed to encourage religious discussion amongst followers, and to increase their critical thinking and their piety.